Application of a digital framework towards the comprehension and restoration of the thin marble envelope of the Casa delle Armi built cultural heritage. (6th July 2021) - Ferrero, Marco; Rosso, Federica; Arena, Gabriella; Vannucchi, Nicola
Cultural heritage sites and architectural heritage are inestimable assets to preserve and play a vital role in the tourism sector of urban areas as well. Therefore, their preservation, usage and maintenance are crucial, so they can be shared with citizens and visitors. Italy is one of the richest countries with respect to the quantity and prominence of cultural heritage and built cultural heritage, and at the same time a significant part of the built heritage is in need of effective restoration strategies. The growth in information technologies (ITs) for both the construction sector and tourism, as well as citizens' life, opens up new scenarios for built heritage preservation, maintenance and enjoyment. The objective of this work is illustrating a digital, BIM-based framework applied towards the preservation of the built heritage. In particular, a famous built heritage, the ' Casa delle Armi ' (Luigi Moretti, 1937), is considered to apply such a framework.